Enhanced simultaneous removal of nitrate and phosphate using novel solid carbon source/zero-valent iron composite - Sun, Haimeng; Qi Zhou; Zhao, Liu; Wu, Weizhong (JOURNAL OF CLEANER PRODUCTION, 2021)
Excessive discharge of nitrate and phosphate to aquatic environment can induce bad eutrophication phenomenon. Simultaneous removal of nitrate and phosphate is challenging for that the low C/N ratios and trace phosphate in wastewater concentration limit advanced nitrate and phosphate removal, respectively. In this study, a novel iron based solid carbon source composite namely solid carbon source/ zero-valent iron was prepared by solid carbon sources and zero-valent iron for advanced simultaneous removal of nitrate and phosphate. The novel composite with 30% zero-valent iron weight ratio presented best simultaneous removal performance with 1.1 +/- 0.1 mg NO3-N/(L.h) and 0.21 +/- 0.07 mg (PO4-P)-P-3/(L.h). The initial pH effects on the removal performance of the novel composite showed that initial pH = 7 remarkably enhanced the nitrate removal (1.1 +/- 0.1 mg NO3 -N/(L.h)) and phosphate concentration declined fastest (0.14 +/- 0.07 mg PO43–P/(L.h)) at initial pH = 5.5. Physical and chemical characterization of the composite confirmed the zero-valent iron oxidation and hydroxidation process after used and phosphate adsorption and precipitation were involved in this process. Microbial communities at genus level on the surface of the composite were identified to be capable of complex carbon hydrolysis and decomposition and denitrification, demonstrating the dominant role of microbial denitrification in nitrate removal. Interestingly, the observation of nitrate reducing Fe(II)-oxidizing bacteria suggested the synergistic effect of autotrophic and heterotrophic denitrification. The novel composite exhibited simultaneous removal of nitrate and phosphate effectively and can be applied in nutrients control in wastewater such as secondary effluent. (C) 2020 Published by Elsevier Ltd.